Pseudostanjehughesia aquitropica gen. et sp. nov. and Sporidesmium sensu lato species from freshwater habitats - Jing Yang (2018)
© 2017 German Mycological Society and Springer-Verlag GmbH Germany Phylogenetic analyses of multi-gene (LSU, SSU, TEF1α, RPB2 and ITS) sequence data support the placement of several Sporidesmium-like species within Sordariomycetes. The taxa collected in the present study were from unidentified submerged twigs in a stream in Prachuap Khiri Khan and Phang Nga Provinces, Thailand and Guizhou Province, China. Morphological examination and phylogenetic analyses provide evidence for several taxonomic novelties, including a new genus (Pseudostanjehughesia) and five novel species (Distoseptispora guttulata, D. phangngaensis, D. suoluoensis, Pseudostanjehughesia aquitropica and Sporidesmium gyrinomorphum). The collections also comprised three previously described species (Distoseptispora multiseptata, Sporidesmium thailandense and S. tropicale). Descriptions and illustrations of the above taxa are provided and their systematic placement is discussed. The description of Distoseptispora is emended.